(Evaluation and Mobility) As Two self-Organizing Posts for University Students (Journal of the College of Education for Women, 2019)
One of the important goals in the learning process is to be effective learning through the self-direction of the learner , because it has an impact on the effort of learners , it is better to be a learner responsible for learning and independent of the acquisition of knowledge ,اذ اكدتكثيرAs many have confirmed منFrom الدراساتStudies والادبياتAnd literature انthat فشلالكثير The failure of many منFrom الطلبةStudents فيin a تنظيمgroup المعلوماتthe information ومعالجتهاAnd processed اثناءduring عمليةProcess تعلمهمLearn them لاNo يرجعReturns الىto me انخفاضdrop فيin a درجةDegree ذكائهمTheir intelligence اوor عدمNon ميلهمTheir inclination للدراسةStudy ,, وانماBut rather يرجعReturns الىto me عدمNon قدرتهمTheir ability علىOn التنظيمOrganization وعدمAnd not تعلمهمLearn them عملياتOperations التخطيطPlanning والمراقبةSurveillance والتقويمAnd calendar والتحكمAnd control فيin a قدراتهمAbilities الذاتيةSelf ويشكلالتنظيمAnd constitutes regulation الذاتيSelf بعداDimension مهماWhatever ومؤثراAnd influential فيin a تحفيزStimulate الذاتSelf فيin a تنظيمgroup المعرفة اثناءKnowledge during المذاكرةstudying بدءاStarting منFrom التهيئةConfiguration والاعدادAnd preparation لتحقيقTo achieve الاهدافObjectives لذاSo فإنP e n امتلاكto have الطلبةStudents لعملياتFor operations التنظيمOrganization الذاتيSelf يساعدهHelp him فيin a السيطرةthe control علىOn تفكيرهمTheir thinking ورفعAnd raise مستوىlevel الوعيAwareness الىto me الحدLimit الذيWhich يستطيعونThey can التحكمcontrol فيهin it وتوجيههAnd directing it بمبادراتهمWith their initiatives الذاتيةSelf ,, وتعديلAnd modification مسارهTrack فيin a الانجازAchievement الذيWhich يؤديLead الىto me تحقيقInvestigation الهدفTarget وانWan الطالبthe student is beingيكون is i اكثرMore ضبطاPress وتحكماًعندماAnd a control when يكونis being علىOn وعيawareness بعملياتOperations تفكيرهHis thinking واساليبAnd styles تعلمهLearn it ,, وقدرتهAnd its ability علىOn بناءBuilding استراتيجياتStrategies تمكنهEnable it منFrom الوصولAccess الىto me اهدافهHis goals المرسومة.Drawn .